PENGUKURAN KUALITAS PELAYANAN PROGRAM PENGUNGKAPAN SUKARELA (PPS) DENGAN METODE SERQUAL-HOQ - Yudha Adi Kusuma (Universitas Putera Batam, 2023)
Public servants contribute in terms of community service. One form of public service program is the Voluntary Disclosure Program (VDP). VDP activities are also carried out on the KP2KP. The implementation of PPS will be carried out between January 1, 2022 and June 30, 2022. During the implementation of the VDP, the number of communities involved was far from the desired number. In this study, measurements were made of service quality in VDP activities at KP2KP XYZ. The number of respondents who were the objects of observation was 150, of which all were the total VDP participants. The results of the questionnaire were then processed using the SERQUAL-HOQ method. Test results related to perception and expectation showed valid (r count > r table) and reliable (cronbach α > 0.6) results. The highest gap between perception and expectation is the accuracy of time in service, with a value of up to 0.3. The results of the HoQ analysis formed 18 attributes from VoC. The development of VoC attributes formed five criteria from technical response. The highest absolute importance value of the technical response is in the timeliness of service, with a value of 135.43.